The role of spheroidal inclusions on the electrical anisotropy of transversely isotrpic rocks. Issue 1 (12th April 2019) - Han, Tongcheng; Xu, Denghui; Fu, Li-Yun; Li, Fulai
SUMMARY: Electrical surveys are among the most important geophysical applications to understand the subsurface Earth, where anisotropic rock matrix is frequently encountered. Knowledge of the electrical properties of such rocks and their relationships with information of geological features included in the anisotropic rocks is crucial for the interpretation of electrical survey data. For this purpose, we first derive rigorous theoretical models for the electrical anisotropy of transversely isotropic (TI) rocks with spheroidal inclusions. The models assume the anisotropic background behaves isotropically in the direction whey the electrical field is applied parallel to the TI axes, and account for both aligned and randomly distributed inclusions and reduce to classical electrical models in the case of isotropic background. We then study systematically, through the obtained new models, the combined effects of geometry, concentration and alignment of both conductive and insulating spheroidal inclusions on the electrical anisotropy of TI rocks. We show that for aligned inclusions, the impact of inclusion volume fraction and aspect ratio is most significant in the direction when the electrical conductivity is measured along and perpendicular to the inclusions for conductive and insulating inclusions, respectively. For randomly distributed inclusions, both horizontal and vertical conductivity increases with decreasing aspect ratio of conductive inclusions and decreases with reducing aspect ratio of insulating inclusions. Most importantly, it is shown that the effects of randomly distributed conductive and insulating inclusions on the electrical anisotropy are similar although the rocks with insulating inclusions exhibit greater electrical anisotropy. The results provide new insights into the roles of spheroidal inclusions on the electrical anisotropy of TI rocks and pave a way for the successful interpretation of electrical survey data acquired in anisotropic rocks.